Combination of two desensitizing protocols to control dentin hypersensitivity in non-carious lesions: a randomized, double-blind clinical trial - Barros, Antonia Patricia Oliveira; de Melo Alencar, Cristiane [UNESP]; de Melo Pingarilho Carneiro, Alexandra; da Silva Pompeu, Danielle; Barbosa, Gabriela Monteiro; Araújo, Jesuína Lamartine Nogueira; Silva, Cecy Martins (Springer Nature, 2022)
Objectives: This study evaluated the effect of photobiomodulation (PBM) combined with 8% strontium acetate (SA8%) in the treatment of dentin hypersensitivity (DH) in non-carious lesions and analyzed the risk factors with the patient’s quality of life. Methods: Eighty teeth with DH were randomly allocated into four treatment groups (n = 20): G1, PBM imitation + toothpaste with no active ingredient; G2, PBM imitation + toothpaste with SA8%; G3, PBM + toothpaste without the active ingredient; and G4, PBM + toothpaste with SA8%. Participants were provided with a questionnaire on the experience of dentin hypersensitivity (QEDH) to assess the impact of desensitizing treatment on health-related quality of life (HRQL). Friedman and Kruskal–Wallis tests were used for intra- and intergroup comparisons, and Wilcoxon and Mann–Whitney tests were used to analyze HRQL. All analyses used significance levels of 5%. Results: Intergroup comparisons revealed a significant difference (p < 0.05); G4 had the best response in terms of HD reduction in G4 compared to the other groups on the 7th day of assessment (T3). Only G4 showed a statistically significant difference (p < 0.05) in the reduction of EDH for intragroup analysis. Conclusion: The combination of therapies was more effective in reducing DH than the isolated use of these strategies. Clinical relevance: The combination of therapies is effective in the treatment of DH.
Keywords: Dentin hypersensitivity; Quality of life; Risk factors; Therapy